Advances in micro-mechanical modeling using a bonded-particle model and periodic homogenization within discrete element framework applied to heterogeneous ceramics. Issue 3 (March 2023) - Asadi, Farid; André, Damien; Emam, Sacha; Doumalin, Pascal; Huger, Marc
Abstract: The Discrete Element Method (DEM) can account for microcracks initiations and propagations within the microstructure and their impact on the macroscopic properties of ceramics. Combing the DEM with the Periodic Homogenization (PH) allows working with a limited number of elements, thus facilitating the multiscale transition of the elastic properties of ceramics: from the microscale (inclusion/pores scale) to the macroscopic elastic behavior of such continuum media. However, the PH approach for a continuum media is currently less developed in DEM than the FEM. Hence, this study aims to consolidate a DEM framework, using a bonded-particle model and PH to improve the prediction of the elastic properties (Cij tensor) of ceramics. Here, a face-centered cubic unit cell is combining‎ with periodic boundary conditions to build a 3D representative volume element in DEM to model the macroscopic elastic properties of model materials and is validated by experimental data, analytical and FEM approaches.